Enhancing English Literature Teaching Through Role-Play Activities - Rakhmatova Zukhro Najmiddinovna (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This article explores the benefits of using role-play activities to enhance English Literature teaching. By integrating role-play techniques into the traditional classroom setting, educators can provide students with immersive, interactive experiences that foster a deeper understanding and appreciation of literary works. The article delves into the key strategies for implementing role-play activities, highlighting their impact on student engagement, critical thinking, and empathy. Additionally, the potential challenges and considerations when integrating role-play into English Literature instruction are discussed. Overall, this article aims to underscore the value of role-play in transforming the teaching and learning experience in English Literature.